Spray-drying process preserves the protective capacity of a breast milk-derived Bifidobacterium lactis strain on acute and chronic colitis in mice - Burns, Patricia Graciela (2017)
Gut microbiota dysbiosis plays a central role in the development and perpetuation of chronic inflammation in inflammatory bowel disease (IBD) and therefore is key target for interventions with high quality and functional probiotics. The local production of stable probiotic formulations at limited cost is considered an advantage as it reduces transportation cost and time, thereby increasing the effective period at the consumer side. In the present study, we compared the anti-inflammatory capacities of the Bifidobacterium animalis subsp. lactis (B. lactis) INL1, a probiotic strain isolated in Argentina from human breast milk, with the commercial strain B. animalis subsp. lactis BB12. The impact of spray-drying, a low-cost alternative of bacterial dehydration, on the functionality of both bifidobacteria was also investigated. We showed for both bacteria that the spray-drying process did not impact on bacterial survival nor on their protective capacities against acute and chronic colitis in mice, opening future perspectives for the use of strain INL1 in populations with IBD.